GLOBAL RATIFICATION GAPS IN THE UN MIGRANT WORKERS CONVENTION: LEGAL RISKS FOR INDONESIAN MIGRANT WORKERS ABROAD - Susanti, Hera; Malwengo, Joel; Sabrina, Yunita; Gunawati, Anne; Rohani, Aceng Asnawi; Solapari, Nuryati; Muksalmina, Muksalmina (Tirtayasa Journal of International Law, 2025)
This article aims to examine the legal and human rights consequences of the low number of countries that have ratified the UN Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families, as well as to analyze the underlying reasons behind the limited participation of labor-receiving countries. This research employs a normative legal approach by analyzing international legal instruments and state practices related to the protection of migrant workers. The findings indicate that the low level of ratification has left migrant workers in non-ratifying countries more vulnerable to various human rights violations, such as unpaid wages, exploitative working hours, physical or sexual abuse, and arbitrary deportation.the limited  ratification hampers the formation of a global protection standard and creates an imbalance of responsibility. One of the main reasons for the reluctance of receiving countries to ratify the convention is the low political prioritization of migrant protection, along with the perception that ratification imposes legal and financial burdens—especially due to the convention’s inclusion of rights for undocumented migrant workers. The scientific contribution of this research lies in its identification of normative and implementation gaps within international legal frameworks concerning migrant worker protection. It offers a critical analysis of structural and political barriers that hinder the establishment of a comprehensive global protection regime. This study contributes to the broader discourse on international law and human rights by highlighting the urgency of legal accountability and shared responsibility among migrant-receiving states in ensuring transnational labor rights protections.